2017
DOI: 10.1371/journal.pone.0173145
|View full text |Cite
|
Sign up to set email alerts
|

Elevated pCO2 enhances bacterioplankton removal of organic carbon

Abstract: Factors that affect the removal of organic carbon by heterotrophic bacterioplankton can impact the rate and magnitude of organic carbon loss in the ocean through the conversion of a portion of consumed organic carbon to CO2. Through enhanced rates of consumption, surface bacterioplankton communities can also reduce the amount of dissolved organic carbon (DOC) available for export from the surface ocean. The present study investigated the direct effects of elevated pCO2 on bacterioplankton removal of several fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 65 publications
4
26
0
Order By: Relevance
“…() showed that elevated p CO 2 stimulated transcript abundance of respiratory proton pumps that aid in translocating protons across the cell membrane, suggesting that bacteria upregulate respiratory proton pumps to export protons that invade the cell as a result of high external p CO 2 . Consistent with our results from seawater culture experiments (James et al, ), Bunse et al . () suggest that upregulating proton pumps may decrease bacterial growth efficiency.…”
Section: Introductionsupporting
confidence: 93%
See 4 more Smart Citations
“…() showed that elevated p CO 2 stimulated transcript abundance of respiratory proton pumps that aid in translocating protons across the cell membrane, suggesting that bacteria upregulate respiratory proton pumps to export protons that invade the cell as a result of high external p CO 2 . Consistent with our results from seawater culture experiments (James et al, ), Bunse et al . () suggest that upregulating proton pumps may decrease bacterial growth efficiency.…”
Section: Introductionsupporting
confidence: 93%
“…In the presence of phytoplankton communities, Bunse et al (2016) showed that elevated pCO 2 stimulated transcript abundance of respiratory proton pumps that aid in translocating protons across the cell membrane, suggesting that bacteria upregulate respiratory proton pumps to export protons that invade the cell as a result of high external pCO 2 . Consistent with our results from seawater culture experiments (James et al, 2017), Bunse et al (2016) suggest that upregulating proton pumps may decrease bacterial growth efficiency. Although this study offers insight to the physiological and phylogenetic responses of bacteria to changes in pCO 2 , predicting how elevated pCO 2 will affect bacteria-mediated carbon cycling requires measurements of organic carbon removal and bacterial growth dynamics.…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations